The politics of crisis management : public leadership under pressure - Boin, Arjen (Cambridge, UK ; New York : Cambridge University Press, 2005)
"Crisis management has become a defining feature of contemporary governance. In times of crisis, communities and members of organizations expect their leaders to minimize the impact of the crisis at hand, while critics and bureaucratic competitors try to seize the moment to blame incumbent rulers and their policies. In this extreme environment, policy makers must somehow establish a sense of normality, and foster collective learning from the crisis experience. In this uniquely comprehensive analysis, the authors examine how leaders deal with the strategic challenges they face, the political risks and opportunities they encounter, the errors they make, the pitfalls they need to avoid, and the paths away from crisis they may pursue.
This book is grounded in over a decade of collaborative, cross-national case study research, and offers an invaluable multidisciplinary perspective. This is an original and important contribution from experts in public policy and international security."--Jacket
Crisis management in political systems : five leadership challenges -- Sense making : grasping crises as they unfold -- Decision making : critical choices and their implementation -- Meaning making : crisis management as political communication -- End games : crisis termination and accountability -- Learning from crises and the politics of reform -- How to deal with crisis : lessons for prudent leadership.
Includes bibliographical references (pages 158-175) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Crisis management in government; Administration publique -- Gestion de crise; POLITICAL SCIENCE -- Public Affairs & Administration; Crisis management in government; Crisisbeheersing; Leiderschap; Electronic books; Electronic books